Twelve-Year Outcomes of an Oxinium Total Knee Replacement Compared with the Same Cobalt-Chromium Design: An Analysis of 17, 577 Prostheses from the Australian Orthopaedic Association National Joint Replacement Registry. (15th February 2017) - Vertullo, Christopher J.; Lewis, Peter L.; Graves, Stephen; Kelly, Lan; Lorimer, Michelle; Myers, Peter
Abstract : Background: Oxidized zirconium (Oxinium) was introduced as an alternative bearing surface to cobalt-chromium (CoCr) in an attempt to reduce polyethylene wear and decrease aseptic mechanical failure of total knee replacements. While noncomparative reports have been described as promising, we were aware of no short or long-term clinical studies showing the superiority of Oxinium on polyethylene as a bearing surface. Using data from a comprehensive national joint replacement registry, we compared the long-term outcomes after cruciate-retaining total knee arthroplasty (TKA) with an Oxinium femoral component and those with the same prosthetic design but with a CoCr femoral component. Methods: The cohorts consisted of 17, 577 cemented Genesis-II cruciate-retaining total knee replacements using non-cross-linked polyethylene, which included 11, 608 with CoCr femoral components and 5, 969 with Oxinium femoral components. The cumulative percent revision and hazard ratio (HR) for revision risk were estimated for the cemented Genesis-II Oxinium and CoCr cruciate-retaining TKAs performed in Australia from September 1, 1999, to December 31, 2013. In addition, the revision diagnoses and the effects of age and patellar resurfacing were examined. Results: No difference in the HR for revision risk was found between the Oxinium and CoCr cohorts for any age category for all causes of revision (HR = 0.92 [95% confidence interval (CI), 0.92 to 1.29]; p = 0.329), loosening or lysis, or aseptic causes, except for loosening or lysis in the group of patients who were ≥75 years old (p = 0.033). In these patients, TKA with Oxinium femoral components had a higher rate of revision. Younger patients preferentially received Oxinium femoral components. The revision risk was not affected by patellar resurfacing or nonresurfacing. At 12 years, the cumulative percent revision was 4.8% (95% CI, 4.2% to 5.4%) for the CoCr Genesis-II prosthesis compared with 7.7% (95% CI, 6.2% to 9.5%) for the Oxinium Genesis-II prosthesis. Conclusions: In this cohort study involving the same prosthetic design, Oxinium femoral components did not reduce revision rates for all causes, loosening or lysis, or when infection as a cause of revision was removed compared with the same CoCr femoral component across all age groups including patients who were <55 years old. The cumulative percent revision was greater for the Oxinium components than for the CoCr components. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.